Effectiveness of Ipomoea aquatica and Pelthoporum pterocarpum for controlling the golden apple snail, Pomacea canaliculata - Latip S. N. H. M.,; M. N. F. Abrahim,; ‘A. S. N. Othman, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2015)
Pomacea canaliculata Lamark (golden apple snail, GAS) which known as siput gondang emas among Malay farmers is dangerous pest to the paddy field feeds on stem and young leaves of paddy plant. Frequently, usage of synthetic pesticides may cause pollution to the environment which became harmful to human and other living things. Hence, to control GAS, the usage of biopesticides is become the most popular control method. Biopesticides formed from animals, plants, bacteria and minerals. About 247 families from 2500 plants have the role of secondary metabolites to protect themselves from the pests. Some of the plants have their own mechanism to protect themselves from enemies like pests, diseases due to its chemical compound, which acts as toxicity to the pest, repellency, antifeedant and insect growth regulatory activities. The aim of this study is to evaluate the effectiveness of Ipomoea aquatica and Pelthoporum pterocarpum extracts for controlling GAS by using different solvents. From the study, methanol extraction showed the highest mortality rather than using ethanol for both plants. It showed that methanol is the most effective solvent due to mortality of the GAS by 50% concentration (24 hours) and 100% concentration (48 hours) is 53.33%. Based on probit analysis, Pelthoporum pterocarpum extracts by using methanol as solvent showed the strongest toxicity test result (LC50 = 4.683%). In the future, Pelthoporum pterocarpum extracts using methanol can be used to replace the usage of synthetic pesticides for controlling GAS.